Determination of the composition of the Zinelbulak talc-magnesite deposit rock using modern physicochemical methods - Jumaniyazov, Maxsud; Kurambayev, Sherzod; Atashev, Elyor; Jumaniyozov, Arslon; Buranova, Mokhigul (E3S web of conferences, 2025)
In this study, the elemental and oxide composition of talc-magnesite raw materials obtained from the Zinelbulak deposit, located in the Sultan Uvays mountain range of Uzbekistan, were investigated using X-ray fluorescence analysis. The results revealed the presence of the following compounds in mass percentages relative to the total mass: talc (3MgO∙4SiO 2 ∙H 2 O) 60.97%, magnesite (MgCO 3 ) 27.74%, dolomite (MgCO 3 ∙CaCO 3 ) 2.90%, chlorite (5MgO∙5FeO∙Al 2 (SiO 3 ) 3 ∙H 2 O) 8.01%, and calcite (CaCO 3 ) 0.38%. The results of the IR spectral analysis of the sample confirm the findings of the X-ray fluorescence and X-ray phase analyses. To further study the composition of the raw material, differential thermal analysis and thermogravimetry methods were employed. A quantitative analysis of particle size during the grinding process of the talc-magnesite raw material from the Zinelbulak deposit was also conducted. The research results indicate the potential for utilizing these new raw material sources in the production of talc and magnesite.